Avaliação da usabilidade do portal do TCE-RN - Endo, Pedro Eidy Pontes (2019)
The Court of Accounts of the State of Rio Grande do Norte (TCE/RN) lacks documentation for its computer systems, which affect the software development and maintenance. Said that, this work aimed to produce a usability guidelines document and use it to evaluate the portal of TCE/RN. The intention is to point out the errors and successes and to suggest improvements to the TCE-RN portal regarding its web usability. From guidelines compiled from consolidated documentation, a checklist questionnaire was produced where users and system developers were able to perform a usability evaluation, thus allowing to define a usability rate for the portal. This research included the following methodological steps: bibliographic study; TCE-RN portal study; guidelines document development; usability checklist production; TCE-RN portal usability analysis; results evaluation and improvements proposal. The method for analysis has the questionnaire methodology and the experimental research approach. Finally, it was concluded that the site met just over half of the proposed usability guidelines. This metric can be improved if the suggestions and the guidelines resulted from this research are followed.